299 The prevalence and role of SCN10A variants in Han Chinese patients with Brugada syndrome: the SADS-TW BrS registry. (13th January 2020) - Chen, C-Y; Liu, Y-B; Lu, T-P; Yu, Q-Y; Lin, L-Y; Yu, C-C; Makita, N; Ishikawa, T; Lai, L-P; Hwang, J-J; Yeh, S-F; Lin, J-L; et al.
Abstract: On Behalf: SADS-TW BrS registry Background: Brugada syndrome (BrS) is an inheritable arrhythmic disease responsible for sudden cardiac death. Information on the prevalence and role of SCN10A variants in BrS is limited and equivocal. Purpose: We aimed to investigate the prevalence and role of SCN10A variants in BrS in Han Chinese. Methods: From 2000 to 2017, we prospectively and consecutively enrolled 176 unrelated BrS patients from the Han Chinese population in Taiwan (the SADS-TW BrS registry). Thirty-four BrS-related genes were screened by next-generation sequencing, using Taiwan Biobank as the population reference. The pathogenicity was evaluated by literature review and in silico analyses, including the SKAT-O algorithm. Results: The SKAT-O algorithm showed that rare variants of SCN10A, but not common variants, were significantly different between BrS patients and healthy controls in the additive and dominant models (p-value <0.001), suggesting that rare SCN10A variants may play a role in BrS. Six likely pathogenic SCN10A variants were found in 6 patients and were compared to 25 pathogenic or likely pathogenic SCN5A variants found in 29 patients. The patients with likely pathogenic SCN10A variants tended to exhibit sudden death in older age and have a shorter QRS interval than those carrying pathogenic or likely pathogenic SCN5A variants or no variants in either gene (p = 0.06, 0.07, respectively). Collectively, the prevalence of likely pathogenic SCN10A variants was 3.4% in Han Chinese patients with BrS in Taiwan. Conclusions: SCN10A likely pathogenic variants were present in 3.4% of Han Chinese BrS patients. Rare SCN10A variants may play a role in BrS, and may have impact on clinical and electrocardiographic manifestations.